Supramolecular Nanostructures Constructed from Cluster-based Hybrid Macromolecules. (June 2020) - Luo, Jiancheng; Sun, Xinyu; Yin, Jia-Fu; Yin, Panchao; Liu, Tianbo
Highlight: Cluster-based hybrid macromolecules via covalent and non-covalent synthetic approaches. Multi-dimensional supramolecular nanostructures are formed in solution. Controllable and responsive self-assembly behavior by tuning solution conditions. ABSTRACT: Molecular clusters are valuable building blocks to synthesize hybrid macromolecules, and consequently achieve diverse supramolecular nanostructures via self-assembly. Hybrid macromolecules can be synthesized by covalently linking different molecular clusters and grafting organic molecules onto cluster surface, or through complexation via non-covalent interactions. Through regulation of solution conditions such as solvent polarity, ionic strength, and type of cations, well-defined hybrids exhibit versatile self-assembled behavior determined by their molecular structures including shape, composition, volume fraction, topology, and surface functionality. The incorporation of molecular clusters into polymers can tune the flexibility and architecture of cluster-based copolymers, which fills the phase diagrams with different molecular packings as well as supramolecular nanostructures. The complexation between molecular clusters and other organic molecules provides a promising approach to construct multi-dimensional nanostructures through non-covalent interactions. Graphical abstract: Image, graphical abstract